Degradation of Toxic Compounds at Low and Medium Temperature Conditions Using Isolated Fungus. Issue 8 (12th May 2016) - Chang, Young‐Cheol; Fuzisawa, Soichiro; Reddy, Motakatla Venkateswar; Kobayashi, Hikari; Yoshida, Eri; Yajima, Yuka; Hoshino, Tamotsu; Choi, DuBok
Abstract : In the present study, a fungal strain isolated from the Antarctic soil was identified as Penicillium sp. CHY‐2 based on its 5.8S rRNA gene sequence analysis. Furthermore, its biodegradation ability towards 13 different toxic compounds such as 4‐butylphenol (4‐BP), 4‐ sec ‐butylphenol (4‐s‐BP), 4‐ tert ‐butylphenol (4‐t‐BP), 4‐nonylphenol (4‐NP), 4‐ tert ‐octylphenol (4‐t‐OP), 4‐chlorophenol (4‐CP), phenol, bisphenol A (BPA), benzene, toluene, xylene, naphthalene, and phenanthrene at low (4°C) and medium (15°C) temperature conditions was evaluated using high pressure liquid chromatography. Among the 13 compounds, the strain CHY‐2 effectively degraded the six compounds i.e ., 4‐BP, 4‐s‐BP, 4‐t‐BP, 4‐NP, 4‐CP, and phenol at 15°C within one week, and at 4°C within 3 weeks. Also CHY‐2 effectively degraded the 4‐t‐OP at 15°C (70%), but not at 4°C (35%). Among different carbon sources tested, glucose was found to be the most suitable and the growth of CHY‐2 at 4°C was slower than at 15°C. Addition of Tween 80 increased the growth and degradation ability of CHY‐2 towards 4‐BP at 4 and 15°C. The metabolites produced during the degradation of 4‐BP were identified by gas chromatography‐mass spectrometry. Also, bacteria present in the Antarctic soil were determined by denaturing gradient gel electrophoresis and the result showed the presence of Pseudomonas and Syntrophus groups of bacteria. Abstract : Alkylphenols are prevalent groundwater contaminants and suspected human carcinogens. Penicillium sp. CHY‐2 isolated from Antarctic soils is a good candidate for alkylphenol degradation in cold regions. A high degradation ratio is obtained when glucose (5 or 10 g/L) is added to the cultures without NaCl. Supplementation of Tween 80 increases the growth and degradation ability of CHY‐2 towards 4‐butylphenol at 4°C.